Cumulative childhood risk is associated with a new measure of chronic inflammation in adulthood. (9th May 2018) - Rasmussen, Line Jee Hartmann; Moffitt, Terrie E.; Eugen‐Olsen, Jesper; Belsky, Daniel W.; Danese, Andrea; Harrington, HonaLee; Houts, Renate M.; Poulton, Richie; Sugden, Karen; Williams, Benjamin; Caspi, Avshalom
Abstract : Background: Childhood risk factors are associated with elevated inflammatory biomarkers in adulthood, but it is unknown whether these risk factors are associated with increased adult levels of the chronic inflammation marker soluble urokinase plasminogen activator receptor (suPAR). We aimed to test the hypothesis that childhood exposure to risk factors for adult disease is associated with elevated suPAR in adulthood and to compare suPAR with the oft‐reported inflammatory biomarker C‐reactive protein (CRP). Methods: Prospective study of a population‐representative 1972–1973 birth cohort; the Dunedin Multidisciplinary Health and Development Study observed participants to age 38 years. Main childhood predictors were poor health, socioeconomic disadvantage, adverse childhood experiences (ACEs), low IQ, and poor self‐control. Main adult outcomes were adulthood inflammation measured as suPAR and high‐sensitivity CRP (hsCRP). Results: Participants with available plasma samples at age 38 were included ( N = 837, 50.5% male). suPAR (mean 2.40 ng/ml; SD 0.91) was positively correlated with hsCRP ( r 0.15, p < .001). After controlling for sex, body mass index (BMI), and smoking, children who experienced more ACEs, lower IQ, or had poorer self‐control showed elevated adult suPAR. When the five childhood risks were aggregated into a Cumulative Childhood Risk index, and controlling for sex, BMI, and smoking, Cumulative Childhood Risk was associated with higher suPAR ( b 0.10; SE 0.03; p = .002). Cumulative Childhood Risk predicted elevated suPAR, after controlling for hsCRP ( b 0.18; SE 0.03; p < .001). Conclusions: Exposure to more childhood risk factors was associated with higher suPAR levels, independent of CRP. suPAR is a useful addition to studies connecting childhood risk to adult inflammatory burden.